Diagnostics of warm dense matter by high-resolution X-ray spectroscopy of hollow ions. (10th December 2014) - Faenov, A. Ya.; Skobelev, I. Yu.; Pikuz, T. A.; Pikuz, S. A.; Kodama, R.; Fortov, V. E.
Abstract: The short review on the possible applications of the hollow ion spectra for the diagnostics of the high-temperature plasma created by intensive laser and particle beams is presented. Because of the hollow ion spectra features are defined mainly by the mechanisms of their excitation, we consider the various types of the high-temperature plasma where different excitation processes are important. It is shown that like ordinary spectral lines, spectra of the hollow ions offer considerable diagnostic opportunities. At the present time, hollow ion spectra are used mainly to investigate plasma heated by X-ray radiation, but the hollow ions must be generated when plasma is heated by fast heavy ion beams too. In this case, the resultant substance state will be also characterized by solid-state density, and some spatial regions of targets will have relatively low temperatures, i.e., will be a nonideal plasma. It is emphasized that hollow ion spectra are promising diagnostic tool for both nonideal plasma and warm dense matter.